Advanced piezoresistive sensor achieved by amphiphilic nanointerfaces of graphene oxide and biodegradable polymer blends. (1st March 2018) - Scaffaro, Roberto; Maio, Andrea; Lo Re, Giada; Parisi, Antonino; Busacca, Alessandro
Abstract: This work focuses on the preparation of a piezoresistive sensor device, by exploiting an amphiphilic sample of graphene oxide (GO) as a compatibilizer for poly (lactic acid) (PLA)-Poly (ethylene-glycol) (PEG) blends. The presence of GO determined a high stiffening and strengthening effect, without affecting toughness, and allowed a good stability of mechanical properties up to 40 days. Moreover, GO endowed the materials with electrical properties highly sensitive to pressure and strain variations: the biodegradable pressure sensor showed a responsivity of 35 μA/MPa from 0.6 to 8.5 MPa, a responsivity around 19 μA/MPa from 8.5 to 25 MPa. For lower pressure values (around 0.16–0.45 MPa), instead, the responsivity increases up to 220 μA/MPa in terms of ΔI/ΔP (i.e. (ΔI/ΔI0 )/P close to 1 kPa −1 ). Furthermore, this novel sensor is able to monitor submicrometric displacements with an impressive sensitivity (up to 25 μA/μm in terms of ΔI/ΔL, or 70 in terms of (ΔI/I0 )/ε). We implemented a model able to predict pressure changes up to 25 MPa, by monitoring and measuring variations in electrical conductivity, thus paving the road to use these biodegradable, ecofriendly materials as low-cost sensors for a large pressure range.